PENERAPAN MEDIA CERITA BERGAMBAR TERHADAP MINAT BACA SISWA KELAS III SD - Habibah, Nadhirotul Ulil (Program Studi Akuntansi IKOPIN, 2022)
This study aims to determine the application of illustrated story media to students' reading interest. This research is motivated by the low interest in reading in elementary school students, especially in lower grade students. Reading needs to be instilled from an early age in lower grade students. Teachers have an important role in the reading process, therefore teachers need to design interesting reading lessons for students. One of them is by using learning media. The right learning media for the reading process is picture story media. Picture story media can attract students' attention and interest in reading. This study uses descriptive qualitative research methods. Data collection techniques used in this study were observation, interview, and documentation. Based on the results of the study, it can be concluded that illustrated story media can increase the reading interest of third grade elementary school students.